2016
DOI: 10.1111/jfpe.12496
|View full text |Cite
|
Sign up to set email alerts
|

Detection of internal qualities of hami melons using hyperspectral imaging technology based on variable selection algorithms

Abstract: Hyperspectral imaging technology was used to assess the soluble solids content (SSC), titrable acidity content (TAC), and firmness of hami melons. The mean spectra were extracted from the regions of interest (ROI) of the hyperspectral images of each hami melon. Spectral data were first pretreated with different preprocessing methods and analyzed using the partial least squares (PLS) method to build calibration models. However, full spectral data contain a great number of redundant and colinear variables that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…In recent years, the nondestructive detection methods for SSC and/or firmness of fruits have been presented (Arendse et al, 2018;Li et al, 2016;Sun et al, 2016). Among them, hyperspectral imaging technology has been widely used to nondestructively determine SSC and/or firmness of fruits, that is, apple (Dong et al, 2016;Hou et al, 2018), pear (Fan et al, 2015;Yu et al, 2018), orange (Zhang et al, 2020), kiwifruit (Hu et al, 2017), blueberries (Leiva-Valenzuela et al, 2013), melon (Zhang et al, 2018), banana (Rajkumar et al, 2012) and lychee (Pu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the nondestructive detection methods for SSC and/or firmness of fruits have been presented (Arendse et al, 2018;Li et al, 2016;Sun et al, 2016). Among them, hyperspectral imaging technology has been widely used to nondestructively determine SSC and/or firmness of fruits, that is, apple (Dong et al, 2016;Hou et al, 2018), pear (Fan et al, 2015;Yu et al, 2018), orange (Zhang et al, 2020), kiwifruit (Hu et al, 2017), blueberries (Leiva-Valenzuela et al, 2013), melon (Zhang et al, 2018), banana (Rajkumar et al, 2012) and lychee (Pu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The CWs mainly concentrated at the region from 700 to 800 nm. It was consistent with absorption peak appearing in Figure 2, which was attributed to the third and fourth overtone of the O-H-and C-H-functional group, respectively [39]. The hyperspectral images of CWs were applied to extracted image features which were further used for prediction models.…”
Section: Cws Selection By Spamentioning
confidence: 62%
“…The apparent absorption peaks at approximately 760 nm appeared on the ARS curves. The 700-780 nm region presented one obvious absorption peak particularly, which could be attributed to the O-H third overtones and C-H forth overtones [38,39]. Because too much noise existed in region of 388-400 nm and 1000-1045 nm in the original ARS and corrected images, the remaining region from 400 to 1000 nm was employed for further analysis.…”
Section: Ars Analysis and Preprocessingmentioning
confidence: 99%
“…11 With increased understanding of NIR spectroscopy, it is found that eliminating redundant variables from the full spectrum can not only simplify the near infrared spectral analysis models, but can also improve the interpretability, the prediction effect and the robustness of the model. 12 The effectiveness of variable selection has been widely verified in various NIR spectroscopic applications in the detection of fruits, such as soluble solids content (SSC) of apple, 13 pear, 14 watermelon, 15 beer, 16 navel oranges, 17 hami melons, 18 and SSC on-line determination of intact apple. 19 Based upon variable selection, the number of variables can be greatly reduced, and the establishment of multivariate calibration model becomes shorter.…”
Section: Introductionmentioning
confidence: 99%